2013
DOI: 10.1007/s11207-013-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Joy’s Law as a Function of Solar Cycle, Hemisphere, and Longitude

Abstract: Bipolar active regions in both hemispheres tend to be tilted with respect to the East -West equator of the Sun in accordance with Joy's law that describes the average tilt angle as a function of latitude. Mt. Wilson observatory data from 1917 -1985 are used to analyze the active-region tilt angle as a function of solar cycle, hemisphere, and longitude, in addition to the more common dependence on latitude. Our main results are as follows: i) We recommend a revision of Joy's law toward a weaker dependence on l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 31 publications
4
68
0
Order By: Relevance
“…A model for preferred longitudes, as exhibited by activity complexes (see 1 An error in the tilt angle analysis of Dasi-Espuig et al (2010) was pointed out by Ivanov (2012), and corrected by Dasi-Espuig et al (2013), where an anti-correlation remained in the normalized Kodaikanal sunspot tilt angles for cycles 15 -21 that they analyzed, and in weakened form in the MWO data. McClintock and Norton (2013) confirmed the existence of this correlation in the MWO data overall, but found that there was no correlation in the northern hemisphere, only in the southern hemisphere. Section 4.5), was also included.…”
Section: Unusual Cycle 23 Minimumsupporting
confidence: 60%
See 1 more Smart Citation
“…A model for preferred longitudes, as exhibited by activity complexes (see 1 An error in the tilt angle analysis of Dasi-Espuig et al (2010) was pointed out by Ivanov (2012), and corrected by Dasi-Espuig et al (2013), where an anti-correlation remained in the normalized Kodaikanal sunspot tilt angles for cycles 15 -21 that they analyzed, and in weakened form in the MWO data. McClintock and Norton (2013) confirmed the existence of this correlation in the MWO data overall, but found that there was no correlation in the northern hemisphere, only in the southern hemisphere. Section 4.5), was also included.…”
Section: Unusual Cycle 23 Minimumsupporting
confidence: 60%
“…They did not report a change of mean tilt angle over the cycle. Stenflo and Kosovichev (2012) have analyzed the Joy's law tilt angle of selected magnetic bipoles over time and found no statistical change in average Joy's law tilts, and Li and Ulrich (2012) found from a long-term study that tilt angles of spots appear largely invariant with respect to time at a given latitude, but they decrease slowly during each cycle following the butterfly diagram (see McClintock and Norton, 2013, on the difficulty and complexity of sunspot tilt measurements).…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 99%
“…From the lack of dependence of the tilt angle on magnetic flux and because after the emergence stops the Coriolis force vanishes yet the bipoles do not appear to relax to the E-W direction but (statistically) to Joy's law, Kosovichev and Stenflo (2008) conclude that "Joy's law reflects not the dynamics of the rising flux tubes but the spiral orientation of the toroidal magnetic field lines below the surface as suggested by Babcock (1961)". As mentioned above, McClintock and Norton (2013) have endorsed this suggestion.…”
Section: Tilt Anglementioning
confidence: 72%
“…The latter, corrected relation, also fits the graph shown by Wang and Sheeley Jr (1991) in their Figure 1, in which sine tilt angle against sine latitude are plotted. It is noteworthy, that recently McClintock and Norton (2013) have used the corrected relation for Joy's law when citing the relations established by Wang and Sheeley Jr (1991) and Leighton (1969). The latter was based on tilt measurements by Brunner (1930), and plotted in Figure 7, right panel.…”
Section: Tilt Anglementioning
confidence: 99%
See 1 more Smart Citation